Evaluate the expression for the given value.

x = 3; y = -5; z = -2

x(yz)^2 - 3(xyz)^0 + 2x^2yz^2 =

3(-5 * -2)^2 - 3(3 * -5 * -2)^0 + 2(3)^2(-5 * -2)^2 =

3 * 100 - 3 * 30 + 2 * 9

300 - 90 + 18 = 228

Nope. I get

3(-5 * -2)^2 - 3(3 * -5 * -2)^0 + 2(3)^2(-5)(-2)^2
= 3(100) - 3 - 18*5*4
= 300-3-360
= -63

Evaluate the expression -4x3y given that x = 2 and y = -7

To evaluate the expression for the given values of x, y, and z, you need to substitute the values of x, y, and z into the expression and perform the calculations according to the arithmetic operations.

Given: x = 3, y = -5, and z = -2

The expression is:
x(yz)^2 - 3(xyz)^0 + 2x^2yz^2

Substituting the values, we get:
3(-5 * -2)^2 - 3(3 * -5 * -2)^0 + 2(3)^2(-5 * -2)^2

Now let's simplify each part of the expression:

First, we evaluate (-5 * -2)^2, which is the result of multiplying -5 and -2, and then squaring the result:
(-5 * -2)^2 = (10)^2 = 100

Next, we evaluate (3 * -5 * -2)^0, which is the result of multiplying 3, -5, and -2, and then raising that result to the power of 0:
(3 * -5 * -2)^0 = (-30)^0 = 1 (Any number raised to the power of 0 equals 1)

Next, we evaluate (3)^2, which is the result of squaring 3:
(3)^2 = 9

Finally, we evaluate (-5 * -2)^2, which is the result of multiplying -5 and -2, and then squaring the result:
(-5 * -2)^2 = (10)^2 = 100

Now, we substitute the simplified values back into the expression:

3 * 100 - 3 * 1 + 2 * 9 * 100

Now we perform the calculations:

3 * 100 = 300
3 * 1 = 3
2 * 9 = 18

Substituting the calculated values:

300 - 3 + 18 = 315

Therefore, when x = 3, y = -5, and z = -2, the expression evaluates to 315.